Clinical Findings and Bacterial Identification in Eight Pythons with Respiratory Disorders in Bali - Govendan, Puveanthan Nagappan; Purbantoro, Steven Dwi; Erika, Erika; Rumbay, Yedija Putra Kusuma Wardhana; Rompis, Aida Louise Tenden (Jurnal Veteriner, 2022)
The study was aimed to identify bacteria associated with upper respiratory disorders in pythons. Epiglottis-tracheal swabs were collected aseptically from eight pythons (Malayopython reticulatus, Python bivittatus, and Python regius) with respiratory disorders. Common clinical signs were presented with frothy nasal discharge, nasal discharge, wheezing, mild coughing, crackle sound and star-gazing. Samples were cultured and sub-cultured on Blood Agar (BA) and MacConkey Agar (MCA). Colonies were identified by performing Gram staining, standard biochemical and phenotypic tests procedures. One colony was identified using API 20NE kit. Of all seven different colonies that were previously isolated, Neisseria sp., Escherichia coli, Staphylococcus sp., Klebsiella sp., and Burkholderia cepacia were identified. We suggest that bacterial infections among captive pythons could be closely related to the immune system because of the commensal flora becoming pathogenic.